KECELAKAAN KERJA DALAM KEGIATAN EKSPLOITASI HUTAN DI KALIMANTAN TENGAH - Maman Mansyur Idris; Soenarno Soenarno (Jurnal Penelitian Hasil Hutan, 1988)
Logging  in Central Kalimantan  is generally mechanized,  utilizing  modern  machines.   Involved  in these activities  are local labourers,  many among  which have not benefited  any adequate  training for  their jobs. They are originally farmers  or farm  labourers,  and most  of them had very little,  if any education.  It is therefore,  not surprising  that  they can't  operate or handle  the machines properly.The logging industry  is characterized  by hard  work requiring,  high skill  and alertness.Shortcomings in these qualities leads to accidents caused by inumerable factors that are constantly  present  in the tropical  high forests. To develop safety programs research is needed to gather information on work accidents at various logging companies through  the years. The aim of  this study  is to find  out about  the effects  of  mechanized  logging systems  on accident  occurrences. The study  was conducted   in Central Kalimantan, resulting  in the following conclusions  :1.    Accident  frequency rate according  to ANSI  standard for 500 labourers ranges from 95 to 151 accident per million  work hours.2.    Accident  severity rate according  to ANSI  standard for 500 labourers ranges from 4, 000 to 8, 000 days  lost per  million  work hours